THE CORRELATION BETWEEN KNOWLEDGE AND BEHAVIOR WITH THE PRESENCE OF HOUSE DUST MITES IN STUDENT BOARDING ROOMS IN EAST CEMPAKA PUTIH AND THE REVIEW OF ISLAMIC PERSPECTIVE - Putra, Hafiz Primadhya; Damayanti, Ndaru Andri; Arsyad, Muhammad (Fakultas Kedokteran Universitas YARSI, 2023)
Introduction: House dust mites (HDM) are the most common allergen found in homes and spread worldwide. The factors that cause TDR life are behaviour and habits that rarely clean the bedroom. Currently, many students still need knowledge and behaviour regarding clean living. This study aims to determine the presence of house dust mites in student boarding rooms and their relationship with students' knowledge and behaviour towards house dust mites. Methods: This research method is quantitative with a cross-sectional approach. This type of research is descriptive correlation research. The population and sample of this study were 50 students in boarding settlements in Cempaka Putih Timur Village, Cempaka Putih District, Central Jakarta. The sample used the Quota Sampling technique. The data collection instrument used a questionnaire. The testing method used is the validity and reliability test using the SPSS application. Data analysis techniques using univariate and bivariate analysis. Results: The results showed that the number of rooms with positive house dust mite presence was less than those with negative house dust mite presence. Than, mattress dust has a higher density of house dust mites. Most students had a good level of knowledge and positive behaviour. Conclusion: There is no significant corelation between knowledge and behaviour with the presence of house dust mites in boarding rooms students. In Islam, a Muslim must have extensive knowledge and good behaviour. Good Muslims will keep themselves and their environment clean so that they are away from sources of disease, including house dust mites.